1999
DOI: 10.2307/3318715
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Behaviour of Stationary Distributions for Countable Markov Chains, with Some Applications

Abstract: Let f Z n , n > 0g be an aperiodic irreducible recurrent (not necessarily positive recurrent) Markov chain taking values on a countable unbounded subset S of R d , ð( . ) its invariant measure and f is a non-negative function de®ned on S. We ®rst ®nd suf®cient conditions under which S f (z)ð(dz) I (the corresponding result for the ®niteness of S f (z)ð(dz) was obtained by Tweedie). Then we obtain lower and upper bounds for the values of the invariant measure ð on the subsets B of S, that is, ð(B). These bounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Next we prove the uniform exponential decay of ν N and ν. Again these results are closely related to existing results in the literature, such as those in [18,25,30], Chapters 6 and 7 of [11], Section 2.2 of [3], or Section 16.3 of [26].…”
Section: Proof Of Theorem 81 (A) and (B)supporting
confidence: 87%
“…Next we prove the uniform exponential decay of ν N and ν. Again these results are closely related to existing results in the literature, such as those in [18,25,30], Chapters 6 and 7 of [11], Section 2.2 of [3], or Section 16.3 of [26].…”
Section: Proof Of Theorem 81 (A) and (B)supporting
confidence: 87%
“…In the zero-drift case with general (oblique) reflections, in the 1980s Varadhan and Williams [29] had showed that the process was well-defined, and then Williams [30] gave the recurrence classification, thus preceding the random walk results of [6,11], and, in the recurrent cases, asymptotics of stationary measures (cf. [4] for the discrete setting). Passage-time moments were later studied in [7,24], by providing a continuum version of the results of [5], and in [2], using discrete approximation [1].…”
Section: Related Literaturementioning
confidence: 99%
“…(2) There is a vast literature on the tail asymptotics of SDs for DTMCs on the integers, cf. [7,15,16,20,29,37,38]. From the relationship between an SD of a CTMC and that of its embedded DTMC [40,42], one can readily estimate the tail of the SD of the DTMC based on Theorem 5.8, when both SDs exist.…”
Section: Quasi-stationary Distributionsmentioning
confidence: 99%